2007
DOI: 10.1002/bem.20344
|View full text |Cite
|
Sign up to set email alerts
|

Influence of a 902.4 MHz GSM signal on the human visual system: Investigation of the discrimination threshold

Abstract: The proximity of a mobile phone to the human eye raises the question as to whether radiofrequency (RF) electromagnetic fields (EMF) affect the visual system. A basic characteristic of the human eye is its light sensitivity, making the visual discrimination threshold (VDThr) a suitable parameter for the investigation of potential effects of RF exposure on the eye. The VDThr was measured for 33 subjects under standardized conditions. Each subject took part in two experiments (RF-exposure and sham-exposure experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
2

Year Published

2010
2010
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 26 publications
0
11
0
2
Order By: Relevance
“…Aside from the frequently investigated attention and memory functions, Maier et al [2004] reported increased auditory temporal-order thresholds, but other studies found no effects of 2G digital signals on visual luminance-discrimination thresholds [Irlenbusch et al, 2007], critical flicker fusion thresholds [Wilén et al, 2006], visuo-motor processing , or saccades . None of the studies on 3G UMTS signals found significant effects on various cognitive functions [Schmid et al, 2005;Regel et al, 2006;Riddervold et al, 2008;Unterlechner et al, 2008;Eltiti et al, 2009].…”
Section: Cognitive Performancementioning
confidence: 97%
“…Aside from the frequently investigated attention and memory functions, Maier et al [2004] reported increased auditory temporal-order thresholds, but other studies found no effects of 2G digital signals on visual luminance-discrimination thresholds [Irlenbusch et al, 2007], critical flicker fusion thresholds [Wilén et al, 2006], visuo-motor processing , or saccades . None of the studies on 3G UMTS signals found significant effects on various cognitive functions [Schmid et al, 2005;Regel et al, 2006;Riddervold et al, 2008;Unterlechner et al, 2008;Eltiti et al, 2009].…”
Section: Cognitive Performancementioning
confidence: 97%
“…One of the critical organs that might be damaged by RF‐EMF is the eye, due to its relative proximity to the radiation source during normal mobile phone use. Many studies focused on possible injuries of monkey, human, or rabbit eyes and the visual system in response to EMF exposure of various intensities, frequencies, and modulations [Lu et al, ; Schmid et al, ; Irlenbusch et al, ]. Cornea and lens of the eye are clearly damaged by excessive temperature rise induced by high specific absorption rates (SAR) [Carpenter, ; Kues et al, ; Kues and Monahan, ].…”
Section: Introductionmentioning
confidence: 99%
“…Changes in various components of the retinal ERG were reported by Yee [] and Lim et al [] in rabbit and human retinas at SAR values of 3.6 and 4 W/kg. No influences were observed on various parameters of human visual perception [Schmid et al, ] and on human discrimination threshold [Irlenbusch et al, ] with 1970 MHz and 902.4 MHz EMF, respectively, both with SAR values below 1 W/kg.…”
Section: Introductionmentioning
confidence: 99%
“…The vast majority of these studies examined the effects of Global System for Mobile Communications (GSM)-like signals [Hamblin et al, 2006;Wilen et al, 2006;Fritzer et al, 2007;Haarala et al, 2007;Irlenbusch et al, 2007;Krause et al, 2007;Regel et al, 2007a,b;Barth et al, 2008;Cinel et al, 2008;Curcio et al, 2008;Kleinlogel et al, 2008;Luria et al, 2009;Wiholm et al, 2009], whereas only a few analysed the impact of Wideband Code-Division Multiple Access/3rd Generation Universal Mobile Telecommunications System (WCDMA/3G UMTS) handset signals on cognitive function [Schmid et al, 2005;Kleinlogel et al, 2008;Unterlechner et al, 2008].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies on the possible effects of RF-EMF of GSM mobile phones on cognition did not find any difference in performance measures between real and sham exposure [Hladky et al, 1999;Croft et al, 2002;Haarala et al, 2003Haarala et al, , 2004Haarala et al, , 2007Hinrichs and Heinze, 2004;Besset et al, 2005;Russo et al, 2006;Cinel et al, 2007Cinel et al, , 2008Fritzer et al, 2007;Irlenbusch et al, 2007;Curcio et al, 2008;Kleinlogel et al, 2008]. On the other hand, there are an almost equal number of studies reporting effects on cognitive functions, however, the effects are not consistent.…”
Section: Introductionmentioning
confidence: 99%